POLA KONSUMSI NUTRISI HARIAN BERBASIS KARBOHIDRAT (Ipomoea batatas (L.) DENGAN KECUKUPAN KEBUTUHAN NUTRISI IBU HAMIL - Danu Indra Wardhana; Awatiful Azza; Cipto Susilo; Savira Nurfitasari; Nadiatul Uzhma (Universitas Muhammadiyah Jember, 2022)
Pregnancy is a physiological condition for a mother, because there will be physical changes that affect the life of a mother during pregnancy. A healthy diet and lifestyle in pregnant women can support the growth and development of the fetus in the womb. This study used a cross sectional approach, with a correlational design to analyze the relationship between modification of carbohydrate consumption and the adequacy of the nutritional needs of pregnant women. The sample was 89 pregnant women obtained by purposive sampling. Data were collected by means of questionnaires, structured interviews, and documentary studies, with a retrospective approach about daily food consumption patterns using the FFQ (food frequency questionnaire) in pregnant women. Data analysis was carried out using chi-square test. The results of this study prove that there is a relationship between modification of carbohydrate consumption and the adequacy of the nutritional needs of pregnant women with a P-value of 0.032 and OR 2.5 meaning that pregnant women who modify their carbohydrate nutritional sources will have a 2.5 times better chance of meeting the nutritional needs of pregnant women compared to pregnant women. which does not modify the source of carbohydrate nutrition. Carbohydrates are important nutrients for both mother and fetus. Adequate carbohydrates can be met through the mother's daily nutrition. Sweet potato as a source of carbohydrates can be used as an alternative nutrient to replace rice.